Strengths and weaknesses of the payroll unit in a public university. The case of UNED, Costa Rica - Ramírez-Camacho, Ericka; Torres-Vindas, Javier Antonio (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To conduct a comprehensive diagnosis of the Payroll Unit of the State Distance University (UNED) of Costa Rica. MATERIAL AND METHOD: This study adopted a qualitative methodological approach, which included conducting semi-structured interviews with key managers and staff related to the Payroll Unit, as well as a thorough review of internal regulations, audit reports, and previous studies. The information analysis was carried out through the coding and thematic categorization of the data. RESULTS: The diagnosis identified strengths such as efforts to digitize employee records and the implementation of specific codes for each movement in personnel actions. However, significant weaknesses were also found, such as the absence of specific internal control standards and low staff turnover in critical functions, which increases operational, financial, and compliance risks. CONCLUSIONS: There is a need to develop and update specific internal control standards for the unit, implement a staff rotation system in critical functions, and complete the digitization of employee records.